The role of local participation in decision-making processes of built heritage conservation: a critical analysis of the role of local community in the current revitalisation process of Erbil Citadel - Jasim, Mohammed Awadh (2019)
Present-day conservation policies of built heritage have undergone dramatic changes, shifting the policy-making mechanism from being deep-seated in the site’s decision-makers towards granting genuine opportunity to its local communities. For the decision-makers, built heritage is regarded as a cultural asset of the site, with a consequent touristic potential for the entire place. This has increasingly induced many conservation policy-makers to dominate the conservation policy formulation, thus marginalising the role entrusted to the locals in the process, making it unable to achieve its goals. Accordingly, heritage global charters started strongly recommending involving the local communities in such processes due to their insightful vision in boosting diverse cultural-related potential to achieve different cultural-led goals. Within this context, this research attempts to indicate the role that local participation can play in enhancing the site’s cultural values in order to serve these goals. In particular, the study explores how the local community of Erbil Citadel in Iraqi Kurdistan can boost a series of decisions made by the current revitalisation policy-makers on its built heritage, particularly the decision to demolish the Babylonian Gate. In fact, the revitalisation policy delivers an array of goals that set the site’s cultural assets as a keystone to achieving them, which in return have sparked resentment of some locals, considering them a source of concern that may threaten the site in the long run. Consequently, local participation here is expected to deepen the revitalisation vision in how to involve and simultaneously maintain the site’s cultural assets in its decisions. In order to meet this aim, the research adopts a mixed methodology of qualitative and quantitative techniques, and thus aims for triangulation of the data so as to increase validity and reduce subjectivity to a minimum. Through the decision of the Babylonian Gate, the research indicates that local participation is unable to demonstrate a concrete contribution that really can support the revitalisation policy. It lacks a critical contemporary reading of those cultural assets of the site that can re-display them in a more feasible performance that can be more responsive and fit with the site’s present-day issues on both urban and architectural levels. The research suggests that although local communities can make possible contributions by referring to the diverse cultural potential and values of built heritage, still their views need to be taken into more thoughtful consideration by conservation policy-makers before forwarding them to the implementation stage.